MULTI-OBJECTIVE OPTIMIZATION DESIGN OF MW WIND TURBINE AIRFOILS - LI YingJue; WEI KeXiang; ZHOU Zhou (Jixie qiangdu)
With the development of wind power generation technology,the requirements for various performances of wind turbines are higher. Aerodynamic noise problem has become a key research direction of the wind power industry. Designed to improve the aerodynamic performance of the blade and reduce noise,this paper aims to improve the aerodynamic performance of the blade and reduce the noise,optimize the airfoil structural equation based on the improved Hicks-Henne function,and combine the multi-objective particle swarm optimization algorithm to optimize the design of the S8035 airfoil. Further more,the optimized airfoils are evaluated using XFOIL software and simulations are conducted to investigate their aerodynamic noise and flow characteristics. The results show that the optimized blade has better aerodynamic characteristics and lower noise,which verifies the feasibility of the design method.